A temporal trophic shift from primary parasitism to facultative hyperparasitism during interspecific competition between two coevolved scelionid egg parasitoids. Issue 24 (20th December 2021) - Haye, Tim; Zhang, Jinping; Risse, Marion; Gariepy, Tara D.
Abstract: Understanding competition between scelionid parasitoids that exploit the same host may provide insight into strategies that allow coexistence on a shared resource. Competition studies typically focus on interactions between native and exotic parasitoids that do not share an evolutionary history; however, coevolved parasitoids may be more likely to demonstrate strategies to avoid or exploit a shared resource. We examined intrinsic and extrinsic competition between Asian Trissolcus japonicus (Ashmead) and T. cultratus (Mayr) (Hymenoptera: Scelionidae) associated with Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) that share an evolutionary history. Interspecific interactions were assessed by providing parasitized egg masses to each species at various intervals post‐parasitism, and measuring host acceptance, developmental suitability, and guarding behaviour. Trissolcus japonicus showed high acceptance of parasitized hosts up to 72 h following oviposition by T. cultratus, despite a very poor developmental outcome. In contrast, T. cultratus generally avoided ovipositing in H. halys eggs containing T. japonicus early‐instar larvae but did not avoid parasitizing H. halys that contained eggs and third instar larvae. The adaptive value of this behaviour was supported by developmental outcome: T. cultratus outcompeted T. japonicus eggs but not early‐instar larvae, and a trophic shift occurred wherein T. cultratus developed as a facultative hyperparasitoid on third instar T. japonicus larvae. Trissolcus japonicus guarded egg masses 8–12× longer and displayed more aggressive interactions than T. cultratus, suggesting T. japonicus is the superior extrinsic competitor. Development as a facultative hyperparasitoid provided a competitive niche for Asian T. cultratus and confirms its instrinsic competitive superiority. This also occurs in a biologically distinct European population of T. cultratus, suggesting that facultative hyperparasitism as a competitive strategy is retained in geographically separated populations that have not coevolved with H. halys or T. japonicus . Abstract : Competition between two co‐evolved scelionid egg parasitoids was evaluated to better understand the competitive strategies that allow these two species to coexist on the same host. Not only was Trissolcus cultratus the superior intrinsic competitor when it was the first species to parasitize an egg mass, but it was also able to develop as a facultative hyperparasitoid on T. japonicus . In contrast, T. japonicus displayed more aggressive interactions and longer guarding times, indicating that it is the superior extrinsic competitor.